Do Poorer Countries Have Less Capacity for Redistribution? - Ravallion, Martin (2012)
Development aid and policy discussions often assume that poorer countries have less internal capacity for redistribution in favor of their poorest citizens. The assumption is tested using data for 90 developing countries. The capacity for redistribution is measured by the marginal tax rate on those who are not poor by rich-country standards that is needed to cover the poverty gap or to provide a poverty-level of basic income, judged by developing-country standards. For most (but not all) countries with annual consumption per capita under $2,000 (at 2005 purchasing power parity) the required tax burdens are found to be prohibitive-often calling for marginal tax rates of 100 percent or more. By contrast, the required tax rates are quite low (1 percent on average) among all countries with consumption per capita over $4,000, as well as some poorer countries. Most countries fall into one of two groups: those with little or no realistic prospect of addressing extreme poverty through redistribution from the "rich" and those that would appear to have ample scope for such redistribution. Economic growth tends to move countries from the first group to the second. Thus the appropriate balance between growth and redistribution strategies can be seen to depend on the level economic development.